Relation of Food Insecurity and Hemoglobin Level in Preschool Aged Children - Élida Mara Braga Rocha; Luiz Carlos de Abreu; Amanda Forster Lopes; Claudio Leone; Patrícia Dore Vieira; Italla Maria Pinheiro Bezerra; Sophia Cornbluth Szarfarc (Anemia)
Background. The iron deficiency anemia is a worldwide public problem, especially in developing countries, related to increased body needs and inadequate supply of iron from the diet. Objective. To analyze the association of food insecurity with hemoglobin concentration and the prevalence of anemia in preschool aged children in the city of Taubaté, São Paulo, Brazil. Methods. A cross-sectional study was conducted with 306 children of preschool age. The nutritional status was assessed according to hemoglobin level and anthropometric indicators. Socioeconomic data and Brazilian Household Food Insecurity Measurement Scale (EBIA) results were obtained from interview with parents. Results. The prevalence of anemia was around 19% of preschool aged children and 41.2% families presented food insecurity. The anthropometric indicators were not associated with food insecurity and even though the bivariate analysis demonstrated that mild food insecurity affects the hemoglobin level, after adjusting the multivariate model this association lost significance (p>0.05). Conclusion. The prevalence of anemia of 19.2% and the household food insecurity was found among 42.2% of the population.